2010
DOI: 10.1016/j.fertnstert.2009.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Changes in circulating levels and ratios of angiopoietins during pregnancy but not during the menstrual cycle and controlled ovarian stimulation

Abstract: OBJECTIVE This study was designed to determine if angiopoietin (ANGPT)-1 and -2 are detectable in the circulation of nonhuman primates and women, and if these levels fluctuate in association with ovarian activity. DESIGN Prospective SETTING National Primate Research Center, medical center and infertility clinic. PATIENTS Adult, female rhesus monkeys; 15 women donating oocytes for infertility treatment. INTERVENTIONS Controlled ovarian stimulation with gonadotropins, removal of the corpus luteum and ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
4
9
0
1
Order By: Relevance
“…In addition, Ang-1, a 70 kDa molecule, predominantly exists in high-order multimers [24], which may be speculated to limit its diffusion capacity across the blood-follicle barrier. Our data support earlier findings by Hurliman et al who reported Ang-1/Ang-2 ratios in serum and follicular fluid during controlled ovarian stimulation in a population of oocyte donors [18]. They found similar Ang-1/Ang-2 ratios in serum and follicular fluid to the ones reported in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, Ang-1, a 70 kDa molecule, predominantly exists in high-order multimers [24], which may be speculated to limit its diffusion capacity across the blood-follicle barrier. Our data support earlier findings by Hurliman et al who reported Ang-1/Ang-2 ratios in serum and follicular fluid during controlled ovarian stimulation in a population of oocyte donors [18]. They found similar Ang-1/Ang-2 ratios in serum and follicular fluid to the ones reported in our study.…”
Section: Discussionsupporting
confidence: 93%
“…The high ANGPT-2:ANGPT-1 ratio in developing follicles in vitro was found in a granulosa cell study, where nonluteinized cells produced more ANGPT-2 than ANGPT-1 during a short-term culture. There is also evidence of similar characteristics in the follicular fluid of "lead" follicles from controlled ovarian stimulation protocols in women [28,29].…”
Section: Angiogenesis and Ovarian Functionmentioning
confidence: 91%
“…Examples have been shown that FGF2 is released by human embryos as well as in gilts. During early human pregnancy, ANGPT-1 mRNA and ANGPT-2 mRNA/protein are also expressed in the syncytiotrophoblast [28], and there is evidence that ANGPT-2 mRNA and protein expression also occur in invasive cytotrophoblast [43]. The ANGPT receptors, Tie-1 and Tie-2, have almost exclusive expression on endothelial cells in humans and other primate species [44].…”
Section: Angiogenesis In Placentation and Embryo Developmentmentioning
confidence: 99%
“…The novel data show that serum levels of Ang-2 are increased during the early stage of gestation while serum levels of Ang-1 and sTie2 are relatively stable throughout the gestation [20], [21], [25], [26], [27], [28].the increase in serum level of Ang-2 during first trimester suggests that Ang-2 is required at the early stage of pregnancy. In addition, this increase of Ang-2 in pregnancy serum coincides with the timing of placental vascularisation and development [18].…”
Section: Discussionmentioning
confidence: 78%